ASSESSING THE ENVIRONMENTAL PERFORMANCE OF SOLID WASTE MANAGEMENT SYSTEMS IN A SUPER SPECIALTY HOSPITAL. - Rajamma, Rajesh Rajappan; Vasudevan, Damodaran Madhavi; Prasad, Geena; Jayadev, Ayona; V. V., Pillay; C. H., Sujatha; G., Lekha (Scientific Culture, 2026)
Super specialty hospitals are resource-intensive healthcare systems that generate substantial quantities of solid waste, placing significant pressure on environmental management infrastructure and regulatory compliance. As the number of patients and the complexity of services increase, effective waste management has become critical for operational efficiency, environmental safety, and industrial sustainability. This study assesses the performance and operational challenges of solid waste management systems in a 1,300-bed super specialty teaching hospital in South India. The analysis is on secondary operational records of daily solid waste generation between 2022 and 2024. A descriptive and time-series analysis design was employed after systematic data cleaning and validation to examine annual and monthly waste generation trends, per-bed-day waste indices, and temporal fluctuations in waste production. The results reveal that the total waste generation over the three years increased from 133,376 kg/bed/day in 2022 to 144,168 kg/bed/day in 2024, reflecting the growing intensity of healthcare operations and services. The findings highlight critical gaps in the existing practices and underscore the need for data-driven decision-making, improved waste segregation, scalable waste-handling infrastructure, and integrated sustainability planning. This study provides empirical insights that can inform hospital administrators and policymakers in strengthening environmentally responsible waste management strategies in large super specialty healthcare institutions.